2016
DOI: 10.1080/09638288.2016.1199741
|View full text |Cite
|
Sign up to set email alerts
|

Identifying non-pharmacological risk factors for falling in older adults with type 2 diabetes mellitus: a systematic review

Abstract: Interventions to reduce falling in older adults with type 2 diabetes mellitus should focus on reducing lower extremity pain, reducing body weight and managing comorbid conditions. Implications for Rehabilitation    Diabetes mellitus:   • Older adults with type 2 diabetes mellitus (DM2) have a higher risk for falling than older adults without.   • Older adults with DM2 are more likely to suffer serious injuries when they fall.   • Comprehensive risk factor identification is necessary for rehabilitation professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…Falling is well acknowledged to be a major health concern for older adults, and is associated with disability, institutionalization and lower QOL . Diabetes has been found to be associated with an increased risk of falling in Western countries . The present study, however, found that the rates of falling and injurious falls were similar to those reported for general populations of Chinese older adults .…”
Section: Discussioncontrasting
confidence: 67%
“…Falling is well acknowledged to be a major health concern for older adults, and is associated with disability, institutionalization and lower QOL . Diabetes has been found to be associated with an increased risk of falling in Western countries . The present study, however, found that the rates of falling and injurious falls were similar to those reported for general populations of Chinese older adults .…”
Section: Discussioncontrasting
confidence: 67%
“…Physical impairments that were identified included severity of impaired physical activities, muscle strength, balance and walking velocity, and diabetes-related complications including peripheral nerve dysfunction and visual impairment. Gravesande and Richardson reviewed the non-pharmacological risk factors for falling in older adults who were 50 years of age or over, with type 2 DM [17]. They reported that the most common risk factors were impaired balance, reduced walking velocity, peripheral neuropathy, and comorbid conditions, such as osteoarthritis and heart disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…Less often considered are complications related to participation in everyday life that occur as a result of T2DM. Falls associated with diabetes are an example of one complication that could greatly impact quality of life, secondary to potential injury (Gravesande and Richardson, 2017) or fear avoidance of meaningful activities (Delbaere et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of diabetes is an independent fall risk factor, and physiological, psychological, and behavioral complications are also associated with increased fall risk in those with diabetes (Roman de Mettelinge et al, 2013). Physiologically, diabetes-related visual comorbidities, lower extremity somatosensory changes, and being overweight are fall risk factors for individuals with T2DM (Gravesande and Richardson, 2017). Visual co-morbidities and lower extremity sensory changes can occur when diabetes is poorly controlled and the lack of control results in damaged blood vessels or peripheral nerves (WHO, 2016).…”
Section: Introductionmentioning
confidence: 99%